2022
DOI: 10.1186/s12941-022-00534-2
|View full text |Cite
|
Sign up to set email alerts
|

Virulence, phenotype and genotype characteristics of invasive group B Streptococcus isolates obtained from Swedish pregnant women and neonates

Abstract: Group B streptococci (GBS) are bacteria that can cause preterm birth and invasive neonatal disease. Heterogeneous expression of virulence factors enables GBS to exist as both commensal bacteria and to become highly invasive. A molecular epidemiological study comparing GBS bacterial traits, genotype and host characteristics may indicate whether it is possible to predict the risk of perinatal invasive GBS disease and more accurately target intrapartum antibiotic prophylaxis. A total of 229 invasive GBS isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The serotype III/ST17 strain was the most prevalent in iGBS, whereas the serotype VIII/ST2 strain was the most common in nGBS. These results are similar to the distribution of iGBS serotypes reported in other countries [13,19]. Furthermore, in our study, serotype III was the dominant, followed by serotypes Ia, Ib, II, and V Pili are cell-wall-anchored appendages on GBS cell surface; they play an important role in bacterial attachment to epithelial cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The serotype III/ST17 strain was the most prevalent in iGBS, whereas the serotype VIII/ST2 strain was the most common in nGBS. These results are similar to the distribution of iGBS serotypes reported in other countries [13,19]. Furthermore, in our study, serotype III was the dominant, followed by serotypes Ia, Ib, II, and V Pili are cell-wall-anchored appendages on GBS cell surface; they play an important role in bacterial attachment to epithelial cells.…”
Section: Discussionsupporting
confidence: 91%
“…Maternal GBS colonization is a major determinant of EOGBS infections in neonates. European studies have shown similarity in serotype distribution between maternal colonized GBS and iGBS, and this nding indicates that EOGBS infection is caused by GBS transmission from mother to newborn [13,14].…”
Section: Discussionmentioning
confidence: 68%
“…We have established a nonhuman primate model in which GBS are inoculated into the choriodecidual space of the lower uterine segment where ascending bacteria are first thought to contact the placenta ( Adams Waldorf et al., 2011a ; Vanderhoeven et al., 2014 ; McAdams et al., 2015 ; Boldenow et al., 2016 ; Coleman et al., 2020 ; Weed et al., 2020 ; Coleman et al., 2021 ). The virulence of the GBS strain is paramount for the outcome of a choriodecidual infection in that strains of higher virulence have a greater likelihood of ascension into the uterus, placental invasion and preterm birth or stillbirth ( Whidbey et al., 2013 ; Boldenow et al., 2016 ; Vornhagen et al., 2016 ; Armistead et al., 2019 ; Brokaw et al., 2021 ; Coleman et al., 2021 ; Furuta et al., 2022 ; Huebner et al., 2022 ). A key GBS virulence factor is the ornithine rhamnolipid pigment (β-hemolysin), which imparts hemolytic activity, which is produced by gene products in the cyl operon ( Spellerberg et al., 1999 ; Pritzlaff et al., 2001 ; Whidbey et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%